Penerapan Strategi Promosi di Media Sosial Instagram Feed dalam Memperluas Jangkauan Pasar UMKM Foodnaku di Kota Malang - Khusnia Fitriani; Ita Rifiani Permatasari (INDO PUBLISHING, 2025)
This research examines the promotional strategies of UMKM (MSME) Foodnaku, a kimbab business in Malang, to identify how this culinary startup can improve its marketing effectiveness and expand its customer reach. Founded in November 2022 by students Nabilla and Khusnia, Foodnaku offers unique kimbab variants topped with specialty sauces (spicy mayo, cheese mayo, bbq mayo) and five filling options. While the business initially gained traction through WhatsApp promotion and event participation, their Instagram account (@foodnaku_) remains underutilized with limited customer engagement, highlighting the need for enhanced digital marketing strategiesThis study employed a descriptive qualitative method to analyze how promotional strategies on Instagram Feed could expand Foodnaku's market reach and using SWOT analysis as a method for analyzing MSME problems. The research focused on the Foodnaku UMKM business, with the owner serving as the primary informant. Data were collected through interview, direct observation of Foodnaku's Instagram activities, and analysis of Instagram insight data. The results showed a 15.28% increase in followers, 30% higher average likes per post, and an 88.89% boost in reach. Paid promotions reached over 7,000 accounts in a month. These findings demonstrated that an improved Instagram Feed strategy effectively expanded Foodnaku's market reach. The study concludes with the right digital marketing approach, UMKM like Foodnaku can signifiantly enhance customers engagement and business growth in the competitive culinary market of Malang.